Germination and Early Seedling Development in Quercus ilex Recalcitrant and Non-dormant Seeds: Targeted Transcriptional, Hormonal, and Sugar Analysis - Romero-Rodríguez, M. Cristina; Archidona-Yuste, Antonio; Abril, Nieves; Gil-Serrano, Antonio M.; Meijón, Mónica; Jorrín-Novo, Jesús V. (Frontiers in Plant Science, 2018)
Seed germination and early seedling development have been studied in the recalcitrant species Quercus ilex using targeted transcriptional, hormonal and sugar analysis. Embryos and seedlings were collected at eight morphologically-defined developmental stages, S0-S7. A typical triphasic water uptake curve was observed throughout development, accompanied by a decrease in sucrose and an increase in glucose and fructose. Low levels of ABA and high levels of GAs were observed in mature seeds. Post-germination, IAA, increased, whereas GA remained high, a pattern commonly observed during growth and development. The abundance of transcripts from ABA-related genes was positively correlated with the changes in the content of the phytohormone. Transcripts of the drought-related genes Dhn3 and GolS were more abundant at S0, then decreased in parallel withincreasingwater content. Transcripts for Gapdh, and Nadh6 were abundant at S0, supporting the occurrence of an active metabolism in recalcitrant seeds at the time of shedding. The importance of ROS during germination is manifest inthe high transcript levels for Sod and Gst, found in mature seeds. The results presented herein help distinguish recalcitrant (e.g. Q. ilex) seeds from their orthodox counterparts. Our results indicate that recalcitrance is established during seed development but not manifest until germination (S1-S3). Post-germination the patterns are quite similar for both orthodox and recalcitrant seeds.